2013
DOI: 10.2298/jsc120829107m
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical treatment of Serbian kaolin clay to obtain high reactive pozzolana

Abstract: Mechanochemical treatment of Serbian kaolin clay was carried out in a planetary ball mill using two different milling media, hardened steel or zirconia vials and balls. The samples obtained with various milling times were characterized by the particle size laser diffraction (PSLD), X-ray diffraction (XRD), differential scanning calorimetry/thermogravimetry (DTA/TGA) and Fourier-transform infrared (FTIR) analyses. Mechanochemical treatment induced amorphization of the kaolinite phase accompanied by dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…The pozzolanic activity index evaluated in after 28 days with a grinding time of 60 minutes was 0.79, and 0.85 after 120 minutes. It was shown that longer grinding times produce finer materials with higher SAI, which seems to contradict the results of Mitrovic et al (2013). It would also be convenient to evaluate if the energy and economic costs of longer grinding times are justified with regard to the benefit obtained in the Pozzolanic Activity Index.…”
Section: Improvement Of the Pozzolanic Reactivitymentioning
confidence: 99%
“…The pozzolanic activity index evaluated in after 28 days with a grinding time of 60 minutes was 0.79, and 0.85 after 120 minutes. It was shown that longer grinding times produce finer materials with higher SAI, which seems to contradict the results of Mitrovic et al (2013). It would also be convenient to evaluate if the energy and economic costs of longer grinding times are justified with regard to the benefit obtained in the Pozzolanic Activity Index.…”
Section: Improvement Of the Pozzolanic Reactivitymentioning
confidence: 99%
“…It should be noted that the long grinding times were specific to the low mechanical load grinding device used in this study. As shown by various other researchers [16,17,25,26], the use of more energy intensive grinding equipment such as disc mills or high speed planetary ball mills enables grinding times of less than 1 h.…”
Section: Materials Selection and Preparationmentioning
confidence: 99%
“…In contrast, little work on the pozzolanic activity of mechanochemically activated kaolinite has been published. The scarce data available seem to indicate that the reactivity of mechanochemically activated kaolinite is similar to or slightly inferior to that of thermally activated kaolinite [25,26]. However, a general description of the effect of mechanochemically activated kaolinite on the hydration reactions and properties of blended cements is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In the first grinding stages, a decrease of particle sizes and an increase in clay surface area are observed, including variations of their porosity. Further grinding causes adhesion of the particles, followed by a decline of the specific surface area, amorphization of the structure, and change in plastic and dispersion properties of clays [19,20]. Mechanical exposure is accompanied by the new active sites appearing at the boundaries of the particles faults and an increase in cation-exchange capacity of the mineral, as often observed for kaolinite and other clay minerals.…”
Section: Chemical Modification Of Clay Minerals and Its Influence On mentioning
confidence: 90%